2016
DOI: 10.18632/oncotarget.11102
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial membrane protein 3 regulates TGF-β signaling activation in CD44-high glioblastoma

Abstract: Although epithelial membrane protein 3 (EMP3) has been implicated as a candidate tumor suppressor gene for low grade glioma, its biological function in glioblastoma multiforme (GBM) still remains poorly understood. Herein, we showed that EMP3 was highly expressed in CD44-high primary GBMs. Depletion of EMP3 expression suppressed cell proliferation, impaired in vitro tumorigenic potential and induced apoptosis in CD44-high GBM cell lines. We also identified TGF-β/Smad2/3 signaling pathway as a potential target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 50 publications
4
74
0
Order By: Relevance
“…Previous studies reported that CpG island hypermethylation in the EMP3 promoter region is frequent in LGGs [28-30]. Moreover, EMP3 promoter hypermethylation is associated with a favorable prognostic significance in OS in patients with oligodendroglial and glioblastoma [29, 31, 32]. In line with previous studies, we found that promoter methylation in EMP3 correlated negatively with its expression and lower EMP3 expression predicted better prognosis in LGGs patients.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies reported that CpG island hypermethylation in the EMP3 promoter region is frequent in LGGs [28-30]. Moreover, EMP3 promoter hypermethylation is associated with a favorable prognostic significance in OS in patients with oligodendroglial and glioblastoma [29, 31, 32]. In line with previous studies, we found that promoter methylation in EMP3 correlated negatively with its expression and lower EMP3 expression predicted better prognosis in LGGs patients.…”
Section: Discussionsupporting
confidence: 90%
“…EMP3 was reported to potentially have an influence on signal transduction and cell proliferation in different cancer cell lines by several studies and the results of our interaction screening further support this hypothesis. To verify if EMP3 has an influence on signal transduction and cell viability we generated cell lines with a stable knockdown of EMP3.…”
Section: Resultssupporting
confidence: 83%
“…EMP3 promoter methylation was significantly associated with IDH1/2 mutations and was a favorable prognostic marker in patients with oligodendroglial tumors . Analogous, in glioblastoma low EMP3 expression also was a favorable prognostic marker, while high expression was associated with shorter patient survival …”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Hyaluronic acid (HA), a main component of the ECM, is a natural ligand to CD44 has been used as a targeting moiety for CD44 overexpressing cancers, facilitating preferential uptake, and potent therapeutic efficacy (Orian, ). Recently, CD44 has also been found to be increased in glioma cells compared to healthy astrocytes (Jun et al, ), and has been implicated to directly impact glioma invasion (Jun et al, ; Pietras et al, ). Quercetin (3,3′,4′,5,7‐pentahydroxyflavone) is a well known anti‐ cancer and anti‐inflammatory flavonoid naturally found in whole grains like brown rice, quinoa, red wine, apples, and several vegetables like elder, capers, red onion, and other natural sources very common in the traditional Mediterranean diet (Ikizler, Erkasap, Dernek, Kural, & Kaygisiz, ).…”
Section: Introductionmentioning
confidence: 99%